System-Level Design Techniques for Energy-Efficient Embedded Systems - Schmitz, Marcus T.; Al-Hashimi, Bashir M.; Eles, Petru; SpringerLink (Online service) (Boston, MA : Springer US, 2005)
System-Level Design Techniques for Energy-Efficient Embedded Systems addresses the development and validation of co-synthesis techniques that allow an effective design of embedded systems with low energy dissipation. The book provides an overview of a system-level co-design flow, illustrating through examples how system performance is influenced at various steps of the flow including allocation, mapping, and scheduling. The book places special emphasis upon system-level co-synthesis techniques for architectures that contain voltage scalable processors, which can dynamically trade off between computational performance and power consumption. Throughout the book, the introduced co-synthesis techniques, which target both single-mode systems and emerging multi-mode applications, are applied to numerous benchmarks and real-life examples including a realistic smart phone.
Background -- Power Variation-Driven Dynamic Voltage Scaling -- Optimisation of Mapping and Scheduling for Dynamic Voltage Scaling -- Energy-Efficient Multi-mode Embedded Systems -- Dynamic Voltage Scaling for Control Flow-Intensive Applications -- LOPOCOS: A Prototype Low Power Co-Synthesis Tool -- Conclusion.
Keywords: Computer science; Computer hardware; Computer-aided engineering; Computer Science; Computer-Aided Engineering (CAD, CAE) and Design; Computer Hardware; Electronic books